Effect of the American College of Surgeons Oncology Group Z0011 trial on axillary management in breast cancer patients in the Australian setting. Issue 5 (27th May 2019) - Ngui, Nicholas K.; Hitos, Kerry; Hughes, T. Michael D.
Abstract: The American College of Surgeons Oncology Group Z0011 Trial demonstrated that early breast cancer patients with positive axillary sentinel lymph nodes treated with breast‐conserving surgery and breast radiotherapy had no additional oncologic benefit of proceeding to an axillary lymph node dissection (ALND). The extent to which practice has changed in Australia remains unclear. The aim of this study was to investigate the effect of the Z0011 trial on the management of positive axillary sentinel nodes at an Australian institutional level. We reviewed all breast cancer cases treated at the Sydney Adventist Hospital over a 10‐year period from 1 January 2008 to 31 December 2017. Patients who fulfilled the Z0011 trial criteria were selected. These patients were divided into two groups according to the year of surgery, before and after 1 January 2011 when the Z0011 study was published. Clinicopathologic data and axillary surgical management were compared. Of the 237 patients fulfilling the Z0011 trial criteria, there were 73 patients before and 158 patients after 1 January 2011. In the earlier group the rate of proceeding to an ALND following a positive sentinel node was 78.1% compared to 43.7% in the latter group ( P < 0.0001). There was a significant decline in the rate of ALND over this 10‐year period ( r = −0.79, P = 0.006). The Z0011 trial has influenced the surgical management of the axilla leading to a significant reduction in the rate of an ALND in patients fulfilling the Z0011 trial criteria at our institution.